AI Empowering cell-cultured meat and fermented protein production: From process optimization to novel ingredient design - Yu Han; Haohan Ding; Xiaohui Cui (Food Bioscience, 2026)

Multimodal large language models for food safety detection within deep learning frameworks: a review - Haohan Ding; Chengcheng Chen; Xiaodong Song; Guanjun Dong; Haoheng Chen; Haoke Hou; Xiaohui Cui; Wei Yu; David I. Wilsone (Food Chemistry, 2026)

Research on solubility prediction method for milk powder quality assessment: based on morphological characteristics - Haohan Ding; Yinghao Yang; Xiaodong Song; Guanjun Dong; Xiaohui Cui; Xueru Zhang; Wei Yu; David I. Wilsone (Food Chemistry, 2026)

Advances on Sporisorium reilianum: microbiology along with chemistry, bioactivity, and application - Yihua Wang; Yansong Meng; Zezhuang Hao; Haohan Yang; Zhixin Shen; Denghui Yu; Ye Wang; Shuguang Guan; Yuling Ding; Yong Li (Folia Microbiologica, 2026)

A federated learning-based Aflatoxin M1 prediction model under a data enhancement strategy - Long Wang; Xiaodong Song; Haohan Ding; Xiaohui Cui; David I. Wilson; Wei Yu; Yinghao Yang; Guanjun Dong (Journal of Food Engineering, 2026)

Machine learning-guided formulation optimization of sugar-reduced ice cream: From sweetener characteristics to texture restoration - Yueteng Hu; Fang Zhong; Haohan Ding; Sarina Bao; Renjiao Han; Caiyun Wang; Jian He; Yixun Xia (Innovative Food Science & Emerging Technologies, 2026)

Artificial intelligence enhances food testing process: A comprehensive review - Haohan Ding; Zhenqi Xie; Wei Yu; Xiaohui Cui; David I. Wilson (Food Bioscience, 2025)

Comprehensive Analysis of the SUMO-related Signature: Implication for Diagnosis, Prognosis, and Immune Therapeutic Approaches in Cervical Cancer - Xing Zhang; Jian Cao; Xiuting Li; Yan Zhang; Wenjing Yan; Bo Ding; Jing Hu; Haohan Liu; Xue Chen; Yamei Nie; Fengying Liu; Ning Lin; et al. (Biochemical Genetics, 2024)

Long-term 4-nonylphenol exposure drives cervical cell malignancy through MAPK-mediated ferroptosis inhibition - Xing Zhang; Wenjing Yan; Xue Chen; Xiuting Li; Bingjia Yu; Yan Zhang; Bo Ding; Jing Hu; Haohan Liu; Yamei Nie; Fengying Liu; Yun Zheng; et al. (Journal of Hazardous Materials, 2024)

Integrated assessment of the pollution and risk of heavy metals in soils near chemical industry parks along the middle Yangtze River - Dong Xu; Zejun Wang; Xiaoyu Tan; Haohan Xu; Dongbo Zhu; Ruili Shen; Kang Ding; Hongcheng Li; Luojing Xiang; Zhibing Yang (Science of The Total Environment, 2024)

Interactive neurotoxicity of environmentally relevant concentrations of polystyrene nanoplastics and butyl methoxydibenzoyl methane on early zebrafish embryos - Ranran Zhou; Haohan Yang; Dao Zhou; Shixin Yang; Zhiqiao Shi; Qijie Jin; Zhuhong Ding (Frontiers in Marine Science, 2022)
Organic ultraviolet filters (OUVFs) and nanoplastics (NPs) are two important new pollutants that coexist widely in freshwater and coastal habitats. Both OUVFs and MPs can be taken up by aquatic organisms and may be toxic or co-toxic. In this study, the neurotoxicity and interaction neurotoxicity of the typical OUVFs butyl methoxydibenzoyl methane (BM-DBM) and polystyrene nanoplastics (PS-NPs) on zebrafish at environmental concentrations were comprehensively investigated at the tissue and molecular levels using transgenic or non-transgenic zebrafish. Results showed that both BM-DBM and PS-NPs induced abnormal expression of developmental genes neurogenin 1 , glial fibrillary acidic protein , Finkel-Biskis-Jinkins osteosarcoma oncogene , growth-associated protein 43 , synapsin IIa , and apoptosis regulator a ( Bcl2a ), Bcl2 associated x and apoptosis-related cysteine peptidase a , neuronal loss, motor neuron axon deletion, neuronal apoptosis and behavioral abnormalities in larvae thus being neurotoxic. BM-DBM also specifically interferes with neurotransmitter systems and affects signaling between neurons. In addition, PS-NPs and BM-BDM exerted synergistic and antagonistic effects in inducing apoptosis in neuronal cells and developmental neurotoxicity, respectively. Our results highlight the neurotoxic risk of PS-NPs and BM-BDM and the complex interactive neurotoxic effects of the two. We anticipate that our study may lay the foundation for ecological risk assessment of OUVFs and PS-NPs and exploration of complex interactions between PS-NPs and hydrophobic organic pollutants.